In vitro characterization and clinical evaluation of skin hydration by two formulations mimicking the skin's natural components. (21st March 2022) - Jacques, C.; Rattier, S.; Bianchi, P.; Angerer, T.B.; Frache, G.; Cattuzzato, L.; Perrin, L.; Villaret, A.; Duran, V.; Noharet, J.; Rouquier, A.; Bessou‐Touya, S.; et al.
Abstract: Background: We have developed innovative base formulations that were designed to mimic the skin with respect to its components and galenic structure. Components include water, proteins, lipids, sugars and minerals. Objectives: We characterized formulations and their skin penetration using in vitro methods and evaluated their impact on skin hydration in a clinical trial. Methods: Scanning electron microscopy (SEM) imaging and X‐ray diffraction were used to analyse formulations as well as formulation impact on the stratum corneum (SC) structure. Mass spectrometry imaging (MSI) was used to compare formulation ingredients with SC components and to detect their distribution in the skin. Clinical studies were performed to confirm effects on skin hydration and investigate potential adverse skin effects (irritation and sensitization). Results: SEM and X‐ray diffraction of the formulations showed that lipids were organized in sheets similar to SC lipids. MSI demonstrated similarities between formulation components and skin constituents, as well as a good penetration into the skin. The formulations did not modify the lamellar organization of the SC lipids, but they increased the relative proportion of the crystallized lipids and some of the amorphous lipids. In in vivo studies, a high level of hydration was maintained over 24 h after application with an intense and 'very good hydration'. Both formulations were shown to be non‐(photo)sensitizers with excellent tolerance. Sensorial evaluation indicated the formulations were not oily or sticky and maintained the skin's suppleness over time. Formulations had a 'nude skin' touch and created a natural protective film. Conclusions: The two formulations were well‐tolerated and increased skin hydration in clinical subjects, an effect that could contribute to the alleviation of sensitive skin. The formulations were shown to resemble the lipid organization of the stratum corneum, as well as penetrate the skin without disrupting the lipid lamella organization.